PTEN expression profiles in colorectal adenocarcinoma and its precancerous lesions - Waniczek, Dariusz; Śnietura, Mirosław; Młynarczyk-Liszka, Joanna; Pigłowski, Wojciech; Kopeć, Agnieszka; Lange, Dariusz; Rudzki, Marek; Arendt, Jerzy (Polish Journal of Pathology, 2013)
The aim of the study was to determine expression of the PTEN suppressor gene in colorectal adenocarcinoma and its precancerous lesions (adenomatous polyps) in correlation with common clinical and histopathological features. Forty-four patients with adenomatous polyps and 32 with primary adenocarcinoma of the colon or rectum were enrolled in the study. They underwent endoscopic removal of polyps or major surgery and postoperative adjuvant chemo- and radiotherapy depending on staging of the disease. No patient had received chemotherapy and/or radiotherapy before the surgery. PTEN expression was evaluated using immunohistochemical staining on paraffin-embedded specimens and compared to clinicopathological features of tumors. In colorectal cancers, PTEN expression was found to be significantly lower than in normal intestinal mucosa and adenomatous polyps. That was associated with complete loss of PTEN expression observed more frequently in colorectal cancer, contrary to reduction of PTEN expression occurring mostly in polyps. A correlation between polyp diameter and loss of PTEN was demonstrated as well as between tumor size and TNM advanced stage and PTEN expression. The obtained results suggest that the PTEN/PI3K/Akt pathway may play an important role in early stages of sporadic colorectal carcinogenesis and reduced PTEN expression in late oncogenesis is associated with some adverse clinical and pathological features.